Boron difluoride functionalized (tetrahydroimidazo[1, 5-a]pyridin-3-yl)phenols: Highly fluorescent blue emissive materials. (November 2020) - Colombo, Gioele; Romeo, Antonio; Ardizzoia, G. Attilio; Furrer, Julien; Therrien, Bruno; Brenna, Stefano
Abstract: Some (tetrahydroimidazo[1, 5- a ]pyridin-3-yl)phenols were reacted with boron trifluoride diethyl etherate and the resulting BF2 -functionalized compounds were fully characterized both in solution using 1 H, 13 C, 11 B, 19 F NMR spectroscopy and in the solid state (infrared, fluorescence, X-ray). When excited with UV light these boron difluoride derivatives show in dichloromethane solution an intense fluorescence emission in the UV region, with λ max of emission varying from 357 to 390 nm. Good absolute quantum yields are recorded for most of the compounds. In the solid state, they are characterized by a strong blue emission (388–435 nm), with high absolute quantum yields (up to 0.68) and x, y color coordinates (CIE 1931) close to those expected for standard blue. Time-Dependent Density Functional Theory (TD-DFT) calculations were used to define the nature of the electronic transitions and excited states involved in the fluorescence process. Highlights: Boron difluoride compounds of functionalized (tetrahydroimidazo[1, 5- a ]pyridin-3-yl)phenols. Blue emissive materials. Good absolute quantum yields and photostability. Density Functional Theory calculations to define the origin of fluorescence.